DEVELOPING METHODOLOGICAL COMPETENCE OF FUTURE TECHNOLOGICAL EDUCATION TEACHERS BASED ON A TRANSFORMATIONAL APPROACH (Scientific journal of the Fergana State University, 2025)
This article discusses the significance of technological education in modern society and the methodological competence of teachers. Due to the rapid development of technologies today, new approaches and methods are being implemented in the education system. The methodological competence of future technological education teachers plays a crucial role in their professional activities, as it is essential to possess the necessary skills to effectively organize the educational process and develop it in accordance with contemporary demands. The transformational approach provides the fundamental theoretical basis for renewing and improving the educational process. This approach enhances the interaction between teachers and students during the educational process and ensures active participation of students. The article deeply analyzes the issues related to the development of methodological competence for future technological education teachers. It highlights the role of modern pedagogical methods and innovative approaches in the educational process. Contemporary pedagogical methods serve to improve the quality of education for teachers. At the same time, they encourage teachers to continuously update their knowledge and skills. This, in turn, enhances the quality of the educational process and ensures students' success. The research findings presented in the article outline the necessary approaches for developing methodological competence in teacher training. Such approaches contribute to the improvement of teachers' pedagogical activities and assist in preparing them in line with modern technologies. As a result, the educational process becomes more effective, and students' knowledge levels increase. Teachers should be provided with opportunities to master and apply modern pedagogical technologies. This, in turn, helps to improve the quality of education, enhance students' interest, and ensure their success. The article reflects the importance of technological education and the necessity of enhancing the methodological competence of future teachers.